Bebida con base de maíz morado (Zea mays L.) edulcadora con stevia (Stevia rebaudiana Bertoni). - Bravo Castro, Jordán Joel (2020)
The purpose of the present investigation was to elaborate a drink based on purple corn (Zea Mays L.) sweetened with stevia (Stevia Rebaudiana Bertoni) "to know what is the acceptability of consumers when adding stevia to the drink, a completely randomized design with bifactorial arrangement (2x4) as the first factor A (purple corn) with percentages of (12.5%) (14%), B (stevia) with percentages of (0.075%), (0.1%), (0.125% ), (0.1%), the sensory analyzes were carried out with semi-trained judges and the following parameters were measured: taste, color, texture, smell, acceptability to choose the best treatment, it was performed by the Tukey test (p≤0.05 ), resulting in the best T4 treatment (12.5% purple corn + 0.15% stevia) for the physicochemical analyzes in pH values, all treatments are in accordance with the NTE INEN 2337 standard, T4 obtained a value of 4.10, in acidity values all treatments are consistent According to the general norm of CODEX STAN 247-200, the acidity values of the investigation are from 0.50 to 0.67. The microbiological analyzes were applied to T4, it was concluded that the best treatment meets all the requirements required by the NTE INEN 2337: 2008, because the absence of pathogenic microorganisms was found, in terms of the unit production cost it has a value of $ 1.63 with a unit sale price of $ 1.88 with a return of 25%. Keywords: acceptability, physicochemical, microbiological and organoleptic analysis.